Mengukur Tingkat Partisipasi Masyarakat Kota Bekasi Dalam Penyusunan APBD Melalui Pelaksanaan Musrenbang 2010 - Satries, Wahyu Ishardino (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
Citizen participation in local development planning should be one measure of the extent of the area to develop the values of good governance of his administration. Citizen involvement in the broad sense should be encouraged both through regulation and the creation of an ideal climate of democratization in the region. Thus, it will increasingly have a growing sense of community to the programs area. To realize these conditions, the forum Musrenbang in the budget process and as a formulator of policy development in the region should be carried out with the correct rules so as to meet the needs of people in the area.